Interferometric signal simulation of spaceborne InSAR system - SUN Zao-yu; LIANG Dian-nong; LU Xing-qiang; ZHANG Yong-sheng (Tongxin xuebao)
In order to supply data to the signal processing study of spaceborne InSAR system,the interferometric signal simulation was studied.At first the geometric model,backscattering model and signal model needed by the simulation was analyzed.Using these models the simulation process was given.Then the relationship between facet number and correlation coefficient was analyzed.The analysis shows that by using right facet number the simulated signal can inter-fere and the correlation coefficient can near its theoretic value.Simulated results can validate this method.